Gestión de las emociones en el entorno familiar de los niños de la Institución Educativa Pública Inicial N° 377 Señor de los Milagros, Requena 2022 - Rengifo Payahua, Samanta Sollage (2023)
The results obtained allow us to answer the question formulated for the research: How is the management of emotions in the family environment of the children of the initial public educational institution No. 377 Señor de los Milagros in Requena in 2022? and the objective was to describe the characteristics of the management of emotions in the family environment of the children of the school. In this sense, the type of descriptive research was considered, with its cross-sectional, field, and univariate design. The unit of analysis was the father of the family, taking 53 of them as population and sample, to whom a questionnaire validated by experts was applied using the survey technique. The findings on the management of emotions in the family environment of the parents of the children of the educational institution indicate that it is of a high level in 64.2% (n=34) of a regular level in 35.8 %(n=19) of them and there were no parents with a low level of emotion management.